Ruthenium-catalysed one-pot regio- and diastereoselective synthesis of pyrrolo[1, 2-a]indoles via cascade C–H functionalization/annulation. Issue 78 (18th September 2017) - Singh, Sukhdev; Butani, Himanshu H.; Vachhani, Dipak D.; Shah, Anamik; Van der Eycken, Erik V.
Abstract : Catalytic, regioselective and diastereoselective synthesis of pyrrolo[1, 2- a ]indoles through a cascade C–H activation and cyclization process. Abstract : A cascade approach has been developed towards dual C–C bond formation via consecutive C–H functionalization/cyclization giving access to pyrrolo[1, 2- a ]indoles in a highly regio- and diastereoselective manner using catalytic [Ru( p -cymene)Cl2 ]2 . The methodology was further expanded to attain pentacyclic structures involving manifold C–C bond creation.